Savereign nations, sovereign subjects Japanese legal culture, animations studies, security and sovereignty - Tolentino, Rolando B. (1998)
The issue of comfort women and the image of women in Japanese animation point to certain attitudes that eventually lead to questions of a nation's souvereign rights. If in legal culture contrary subjects like comfort women are negated, other forms of engagement with power need to be established.
Keywords: Japanese; Filipina Comfort Women